PENINGKATAN MINAT DAN HASIL BELAJAR IPA MELALUI STRATEGI WORD SQUARE PADA SISWA KELAS V DI SD NEGERI 03 JETIS KECAMATAN JATEN KABUPATEN KARANGANYAR TAHUN AJARAN 2013/2014 - Ratnasari Diah Utami; Arum Oktavia Sari (Profesi Pendidikan Dasar, 2014)
The purpose of this study was to describe the enhancement of interest and learningoutcomes of students in learning science through the Square Word strategy . This researchis Classroom Action Research ( CAR ). Teacher is as the subject of the perpetratorand the student is as the recipient of actions. Techniques of data collection are usingobservation techniques, interviews, test, and documentation. Technical analysis of thedata is using interactive analysis technique that consists of data reduction, data display,and conclusions. The results of this study showed an increase in interest and learningoutcomes of students in learning science. It can be seen from the indicators of achievementof learning interest include: participation, attention, and pleasure in learning activities.The percentage of participating students’ interest in learning activities increasedfrom 39.53 % to 86.04 %.. Students who are concerned in learning activities in the precycle of 34.88 %, increasing to 83.71 % in the second cycle . While students are happy inlearning activities in pre-cycle by 30.23 % increased to 81.39 % in the second cycle.Student learning outcomes also increased, prior to the act the learning outcomes is asmuch 37.20 % and increased to 81.39 % in the second cycle . This study suggests thatthe implementation of Square Word Strategy can increase the interest and learning inscience teaching at fifth grade students of SD Negeri 03 Jetis District of CorkKaranganyar Academic Year 2013/2014 .